2018
DOI: 10.1016/j.rvsc.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses to metabolic stress can be detected in rumen fluids

Abstract: Many production diseases of dairy cows are related to digestive troubles. The rumen subacute acidosis is the most relevant one, albeit not easily recognized. Recent studies suggest that forestomachs can perform regulatory actions at both regional and systemic levels, since forestomach walls express immune receptors and cytokines, and the rumen liquor is infiltrated by leukocytes. Therefore, the rumen fluid could be conveniently collected for investigating metabolic production diseases. Thus, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
2
18
1
Order By: Relevance
“…As indicated above, ketotic animals in our study had preeclampsia-like conditions; interestingly, the condition of preeclampsia is known to weaken the body defenses (Cornelius, 2018). If such effects oc-curred in the early dry period (or even before), they could have allowed bacterial cell components to enter the organism (Trevisi et al, 2018), challenging immune cells and inducing a condition of endotoxin tolerance in them. This is a protective mechanism against overexuberant inflammation that could have developed when the WBC faced an endotoxin challenge.…”
Section: An Attenuated Response Of Wbc To Lps and Possible Immunosuppression Are Found In Postpartum Ketotic Cowsmentioning
confidence: 54%
“…As indicated above, ketotic animals in our study had preeclampsia-like conditions; interestingly, the condition of preeclampsia is known to weaken the body defenses (Cornelius, 2018). If such effects oc-curred in the early dry period (or even before), they could have allowed bacterial cell components to enter the organism (Trevisi et al, 2018), challenging immune cells and inducing a condition of endotoxin tolerance in them. This is a protective mechanism against overexuberant inflammation that could have developed when the WBC faced an endotoxin challenge.…”
Section: An Attenuated Response Of Wbc To Lps and Possible Immunosuppression Are Found In Postpartum Ketotic Cowsmentioning
confidence: 54%
“…The authors concluded that the digestive system and its host need several weeks to adapt to the new feeding system. Gut health can be influenced by diet, microflora, immune system and intestinal integrity [12,13,46,47]. It plays a major role in dairy farming and is essential for production [46,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to inflammation of the papillae and thus to the activation of an immune response. Trevisi et al [12,13] hypothesized in their study that forestomachs can sense sterile and infectious stressors and react to them, and that there and elsewhere in the body immune response can occur in case of local inflammation or inflammatory conditions, too.…”
Section: Introductionmentioning
confidence: 99%
“…While the information regarding rumen-associated lymphoid tissues is limited, rumen fluid leukocyte populations (including monocytes, T and B cells) are likely to play a significant role in regulation of cattle immune and biochemical parameters ( 50 ). So, CD45 gene expression in rumen fluids (indicative of leukocyte infiltration) negatively correlated with ruminal pH, while the frequencies of B cells (as well as numbers of total IgG and IgM) were negatively affected by ruminal pH and high concentrations of volatile fatty acids.…”
Section: Mucosal Immune Systemmentioning
confidence: 99%
“…Further, some findings suggest that release of fetal membranes can be an immune/hormone-mediated process because increased incidence of retained placenta (RP) is observed in cows sharing MHCI antigen specificity with their calves ( 127 ). It is well established that daily food intake decreases (~30%) as calving approaches ( 128 ), which coincides with increases in levels of pro-inflammatory cytokines ( 50 ). Dairy cows do not consume enough nutrients to meet the increased demand to support lactation which leads to a negative energy balance (NEB).…”
Section: Immune Function In Pregnancy and Early Parturitionmentioning
confidence: 99%